New technology of semi-axles production - A. V. Stepanenko; V. A. Korol (Литьë и металлургия, 2002)
The new technology of production of semi-axles for automobiles of class MAZ, including manufacturing of slug with prefluting and their postrunning-in, is offered. The distinctive feature - simplicity and reliability of operation and possibility of increase of warping degree.